Analisis ANALISIS PENGARUH NILAI TUKAR, TINGKAT SUKU BUNGA DAN HARGA EMAS TERHADAP INDEKS HARGA SAHAM GABUNGAN: PENDAHULUAN - Pujo Gunarso, Pujo Gunarso (STIE Madani Balikpapan, 2024)
The aim of this research is to determine and analyze the influence of the rupiah exchange rate, interest rates and real assets on composite index returns in Indonesia. This research uses quantitative methods. The analysis method uses a multiple linear analysis model using 3 independent variables and one dependent variable. This research is quantitative research using descriptive tests and hypothesis testing for data analysis using SPSS 23 software. Monthly closing price data for the period January 2020 to December 2023 for IHSG share prices, exchange rates, interest rates and real assets. The research results show that only the rupiah exchange rate index has a negative effect on the composite stock price index (IHSG). Meanwhile, real asset returns on gold prices and interest rates have no effect on the Composite Stock Price Index (IHSG).